Insight on the mechanical properties of hierarchical porous calcium-silicate-hydrate pastes according to the Ca/Si molar ratio using in-situ synchrotron X-ray scattering and nanoindentation test. (15th February 2023) - Im, Sumin; Jee, Hyeonseok; Suh, Heongwon; Kanematsu, Manabu; Morooka, Satoshi; Choe, Hongbok; Yuhei, Nishio; Machida, Akihiko; Kim, Jihoon; Lim, Seungmin; Bae, Sungchul
Highlights: Relationship between the hierarchical structure and mechanical properties of C-S-H pastes in the three level-length scales was investigated. Deformation of C-S-H pastes according to Ca/Si ratio at the macro scale was contrary to those at the micro- and nano-scales. The stress–volumetric strain curves of the C-S-H pastes exhibited a strain-hardening behavior. E modulus of the C-S-H pastes was larger at the nano-scale than at the macro-scale. Abstract: Nanocrystalline calcium–silicate–hydrate (C-S-H) is a typical heterogeneous material with a multiscale structure spanning a wide length scale from angstrom to micrometer, and whose structure is determined by the Ca/Si ratio. In this study, we directly applied compressive loads on synthetic C-S-H pastes with Ca/Si ratios of 0.6–1.2 and investigated their mechanical properties using the elastic modulus calculated at three length scale levels (i.e., angstrom to nanometer, micrometer, and millimeter) via in-situ synchrotron X-ray scattering, nanoindentation tests, and strain gauges, respectively. Further, 29 Si nuclear magnetic resonance spectroscopy was conducted on the C-S-H pastes to elucidate the alterations in the silicate polymerization. The experimental results confirmed the deformation behavior of the C-S-H paste with different Ca/Si ratios under external loading, which was demonstrated to be transferred from the surface of the pastes to particles owing to the presence of multiscale pores.